E-Wallets and Financial Literacy: Shaping Gen Z Wasteful Behavior in Indonesia - Rozaq Syamsul Hidayatullah; Mahameru Rosy Rochmatullah (Majapahit Journal of Islamic Finance and Management, 2025)
This study finds that among the tested variables, Love of Money, Machiavellianism, Religiosity, and Tax Knowledge, only Love of Money has a significant influence on tax evasion among accounting students. This highlights the central role of personal financial values in ethical decision-making, suggesting that when monetary gain is prioritized excessively, it can override normative considerations such as compliance and integrity. The non-significance of Machiavellianism, Religiosity, and Tax Knowledge indicates that mere possession of knowledge or personal belief systems may not be sufficient to deter unethical behavior, possibly due to weak internalization or external pressures. These findings underscore the importance of embedding ethical reflection and value-oriented education in accounting curricula, not just focusing on technical competence. Future studies should explore psychological and contextual variables such as peer influence, perceived fairness of taxation, or institutional trust to develop a more comprehensive understanding. Expanding the methodological approach through qualitative interviews and broader sampling would also enhance the richness and generalizability of the results.